Monopolizing Religious Blasphemy Law Interpretation in Indonesia: The Strategy of Lawfare and the Exercise of Power (Mazahib, 2019)
The article explores the process of monopolizing Blasphemy law interpretation by several Islamist groups and its impact on the freedom of religion in Indonesia. Even though the result of blasphemy cases in the national context is predictable, the local context shows a different dynamic. This article examines several religious blasphemy cases locally, such as Otto Radjasa’s in Balikpapan, Sukmawati’s in Jakarta, and Ganjar Pranowo’s in Central Java. It seeks to answer how has religious blasphemy been defined and interpreted by the Islamist group and how each interest has influenced the group interpretation and strategy to bring the offenders of the blasphemy law to the jail. It argues that monopolizing the law interpretation consists of two main strategies: first, by using lawfare against the political rivals, and second, by employing the exercise power while taking financial advantages from the offenders. The article contributes to the academic discussion on the exercise of power and hegemony in influencing the blasphemy law interpretation in Muslims majority countries.Keywords: Religious Blasphemy, Islamists, Power, Hegemony